Evaluation of association of vitamin D level with types of proximal femoral fractures in elderly patients - Khan, Afroz Ahmed; Kumar, Vipin; Yadav, Ashok Kumar; Singh, Robin; Chauhan, Karn Singh; Hasan, Areeba (International Journal of Research in Orthopaedics, 2018)
Background: Proximal femoral fractures are very common in elderly patients. These fractures are thought to be associated with osteoporosis. Vitamin D is a possible risk factor for osteoporosis. So, this study was done to evaluate the association of serum vitamin D level with types of femoral fractures in elderly patients. Methods: The study was done between September 2013 to August 2016, 75 patients with age >60 years (male and female both) with proximal femoral fractures were studied. Serum 25-hydroxy vitamin D, calcium, phosphate, alkaline phosphatase levels, liver function test, renal function test, hemoglobin and complete blood counts of all the patients were assessed. Results: On assessment of serum vitamin D in proximal femoral fracture in elderly patients, it shows an increase incidence of proximal femoral fractures in patients with low serum vitamin D level. Fracture of neck of femur was most common among all. Type of fracture has no significant statistical relationship with serum vitamin D levels. Conclusions: Osteoporosis and serum vitamin D level depends on age and sex of the patient. But type of proximal femoral osteoporotic fracture has no association with either grade of osteoporosis or serum vitamin D level.